Modeling Stock Data Using Multiple Linear Regression and LASSO Regression Analysis - Daniel, Adashu Jacob; Ibrahim, Musa Dahiru; Josaphat, Anule Aondulum (Darul Yasin Al Sys, 2025)
This study evaluates and compares the model fitting and predictive performance of Multiple Linear Regression (MLR) and Least Absolute Shrinkage and Selection Operator (LASSO) regression in the context of stock price prediction for four leading Nigerian companies. A dataset comprising 1,300 observations from 2019 to 2025 was obtained from Yahoo Finance and Investing.com. Multicollinearity assessment using the Variance Inflation Factor (VIF) revealed substantial collinearity among certain predictors, particularly for the variables